Pemanfaatan Feromon Untuk Pengendalian Lalat Buah (Bactrocera Spp.) Pada Masyarakat Desa Mojowiryo - Dimas Ganda Permana Putra; Dipa Aditya; Clarista Ines Maharani; Dita Umrotul Khasanah; Komang Ayu Dewanti; Peggy Tri Rahma; Amelia Tharisa Putri Sutrisna; Swanda Yonia Putri; Sholikah Nur Istianah; Ahmad Andriansyah; Heskya Heskya; Achmad Fikri Wahyu Irsyadi; Kiki Firmansyah Febrianto; Alfiana Alfiana; Sofita Elysa (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The Community Service Program of the Thematic Science KKN (Student Community Service) of Universitas Mayjen Sungkono in Mojowiryo Village. Mojowiryo Village is an agrarian village where the majority of the population relies on agriculture for their livelihood. As one of the villages with agriculture as the maineconomic pillar, the community of Mojowiryo Village often faces significant challenges in pest control, particularly from fruit fly pests (Bactrocera spp.), therefore, the introduction of pheromone technology is necessary to enhance the community’s understanding of environmentally friendly pest control methods. The method used in this community service activity is Participatory Learning and Action (PLA), which involves a participatory approach to learning and practice. The research sample consisted of 20 participants in a pheromone pest control training, characterized by their age, education level, land area, seasonal income, and farming experience. The research results show that the community of Mojowiryo Village strongly agrees with the use of pheromones and their benefits.